1989
DOI: 10.2118/17852-pa
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Aspects of Ekofisk Subsidence

Abstract: Summary In Nov. 1984. Phillips Petroleum Co. discovered subsidence of the seabed overlying the Ekofisk oil reservoirs offshore Norway. This phenomenon is the result of the compaction of the porous chalk reservoirs and the transmission of this compaction through the overburden to the seafloor. This paper describes the geologic- and reservoir-related aspects of subsidence, including the mechanism leading to reservoir compaction and its effect on reservoir performance. The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Of particular interest for this presentation are engineered subsurface systems, such as CO 2 storage, oil‐ and gas production, and geothermal energy recovery. As concrete examples, the uplift at the In Salah storage site has potential to be an important monitoring mechanism , producing oil fields have experienced costly subsidence , and the long term poro‐mechanical evolution, particularly with respect to fracture aperture changes, is critical for assessment of marginal geothermal resources .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest for this presentation are engineered subsurface systems, such as CO 2 storage, oil‐ and gas production, and geothermal energy recovery. As concrete examples, the uplift at the In Salah storage site has potential to be an important monitoring mechanism , producing oil fields have experienced costly subsidence , and the long term poro‐mechanical evolution, particularly with respect to fracture aperture changes, is critical for assessment of marginal geothermal resources .…”
Section: Introductionmentioning
confidence: 99%
“…13 is the assumption that σ v , α and ν all remain constant. However, it has been shown in the literature 22,23 that α and ν are stress dependent and that σ v may not remain constant during production due to stress arching effects in the overburden 24 . These may cause K o to change with depletion 25 , which is scenario that was not considered in this study.…”
Section: Compressibilitiesmentioning
confidence: 99%
“…It has been suggested that stress cycling a sample between some (lower) nominal effective stress and its initial in-situ stress until all hysteresis is dissipated repacks and reorients the sand grains to a state closer to that actually occurring in the subsurface. Two corollary hypotheses are that (1) stress cycling may accelerate the attainment of mechanical equilibrium at initial stress conditions, and (2) stress cycling may provide more accurate mechanical and petrophysical measurements at initial in-situ and higher stresses.…”
Section: Measurement Issuesmentioning
confidence: 99%